2011
DOI: 10.1016/j.bcp.2010.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological and dietary modulators of paraoxonase 1 (PON1) activity and expression: The hunt goes on

Abstract: Paraoxonase 1 (PON1) is a high density lipoprotein (HDL)-associated enzyme displaying esterase and lactonase activity. PON1 hydrolyzes several organophosphorus (OP) insecticides and nerve agents, a number of exogenous and endogenous lactones, and metabolizes toxic oxidized lipids of low density lipoproteins (LDL) and HDL. As such, PON1 plays a relevant role in determining susceptibility to OP toxicity, cardiovascular diseases and several other diseases. Serum PON1 activity in a given population can vary by at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
117
1
13

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 171 publications
(134 citation statements)
references
References 98 publications
3
117
1
13
Order By: Relevance
“…In the present study, administration of simvastatin evening or morning increased PON1 activity compared to baselines. Likewise, Costa et al (2011) reported that simvastatin treatment was increased PON1 activity. However, evening simvastatin administration caused significant increase in PON1 activity compared to morning dosing.…”
Section: Discussionmentioning
confidence: 95%
“…In the present study, administration of simvastatin evening or morning increased PON1 activity compared to baselines. Likewise, Costa et al (2011) reported that simvastatin treatment was increased PON1 activity. However, evening simvastatin administration caused significant increase in PON1 activity compared to morning dosing.…”
Section: Discussionmentioning
confidence: 95%
“…Firstly, considering the factors that have been described to influence PON1 activity (for a review, see [44]) limitations of our study include lack of information on nutrition and alcohol consumption. Secondly, this is a cross-sectional study and therefore we cannot assert causality.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a significant elevation in the plasma PON1 activity and the HDL-C level has been observed in hypercholesterolemic subjects, in response to anthocyanins at a dose of 160 mg two times daily [97]. It could not be excluded that substances with antioxidant potential -vitamin C and anthocyanins, but also polyphenols and vitamin E -prevent PON1 oxidation and in this way support the HDL-C functionality [18].…”
Section: Effect Of Diet On Paraoxonase 1 and Myeloperoxidase Activitiesmentioning
confidence: 99%